2011
DOI: 10.1111/j.1751-7915.2011.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐palladium: from metal recovery to catalytic applications

Abstract: SummaryWhile precious metals are available to a very limited extent, there is an increasing demand to use them as catalyst. This is also true for palladium (Pd) catalysts and their sustainable recycling and production are required. Since Pd catalysts exist nowadays mostly under the form of nanoparticles, these particles need to be produced in an environment‐friendly way. Biological synthesis of Pd nanoparticles (‘bio‐Pd’) is an innovative method for both metal recovery and nanocatalyst synthesis. This review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 64 publications
1
91
0
Order By: Relevance
“…Different strategies have been explored to prevent leaching of the bio-catalyst from bioreactors, such as membrane systems (hollow and plate membranes) (Forrez et al 2011;Hennebel et al 2009a;Mertens et al 2007) and encapsulation in polymeric matrices (polyurethane, polyacrylamide, alginate, silica, etc.) (Hennebel et al 2009b) involving important costs (De Corte et al 2012). Moreover, Suja and colleagues (Suja et al 2014) demonstrated that interaction between biogenic Pd(0) and aerobic granular sludge promoted the reduction of p-nitrophenol and Cr(VI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies have been explored to prevent leaching of the bio-catalyst from bioreactors, such as membrane systems (hollow and plate membranes) (Forrez et al 2011;Hennebel et al 2009a;Mertens et al 2007) and encapsulation in polymeric matrices (polyurethane, polyacrylamide, alginate, silica, etc.) (Hennebel et al 2009b) involving important costs (De Corte et al 2012). Moreover, Suja and colleagues (Suja et al 2014) demonstrated that interaction between biogenic Pd(0) and aerobic granular sludge promoted the reduction of p-nitrophenol and Cr(VI).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this concept, several studies have reported on the use of pure microbial cultures for achieving Pd(II) reduction for the recovery of Pd(0) (De Corte et al 2012;De Windt et al 2005;Lloyd et al 1998;Mikheenko et al 2008;Pat-Espadas et al 2013;Yates et al 2013). Microbially driven reduction of Pd(II) is now considered as a viable alternative since it implies a process with less aggressive conditions and fairly easy manipulation and avoids the production of toxic by-products (Macaskie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…production costs and the need for stable nanoparticulate catalysts for high activity have led to the recognition of biogenesis as a means to synthesise precious metal-nanoparticles (NPs) supported on bacteria de Corte et al 2012). Bio-Pd-NP catalysts combine the benefits of homogeneous and heterogeneous catalysis (Creamer et al 2007) with the stabilization of the Pd-NPs against agglomeration and permit their re-use without attrition or loss (Bennett et al 2013).…”
mentioning
confidence: 99%
“…However PMs can be bio-refined from wastes into new catalytic materials (e.g. reviews by Macaskie et al 2011;Deplanche et al 2011;De Corte et al 2012), the activity of which can be comparable to (or exceed) that of pure metal catalysts (Mabbett et al 2006;Yong et al 2010;Macaskie et al 2011;Murray et al 2015).…”
mentioning
confidence: 99%
“…However, these waste streams can also contain valuable metals such as platinumgroup metals [5,6], silver, gold [7], gallium, indium, rareearth elements (REEs) [8][9][10][11][12], or uranium [13,14]. The recovery of valuable metals from dilute aqueous waste streams processing from acid mine drainage, coal mines [15], from industrial effluents, or from treatment of spent materials (wastes and end-of-life consumer goods) comes like complementary to primary mining resources [14,16,17].…”
Section: Introductionmentioning
confidence: 99%